Proteoglycans and glycosaminoglycans as regulators of cancer stem cell function and therapeutic resistance. (27th June 2019) - Vitale, Daiana; Kumar Katakam, Sampath; Greve, Burkhard; Jang, Bohee; Oh, Eok‐Soo; Alaniz, Laura; Götte, Martin
Abstract : In contrast to the bulk of the tumor, a subset of cancer cells called cancer stem cells (CSC; or tumor‐initiating cells) is characterized by self‐renewal, unlimited proliferative potential, expression of multidrug resistance proteins, active DNA repair capacity, apoptosis resistance, and a considerable developmental plasticity. Due to these properties, CSCs display increased resistance to chemo‐ and radiotherapy. Recent findings indicate that aberrant functions of proteoglycans (PGs) and glycosaminoglycans (GAGs) contribute substantially to the CSC phenotype and therapeutic resistance. In this review, we summarize how the diverse functions of the glycoproteins and carbohydrates facilitate acquisition and maintenance of the CSC phenotype, and how this knowledge can be exploited to develop novel anticancer therapies. For example, the large transmembrane chondroitin sulfate PG NG2/CSPG4 marks stem cell (SC) populations in brain tumors. Cell surface heparan sulfate PGs of the syndecan and glypican families modulate the stemness‐associated Wnt, hedgehog, and notch signaling pathways, whereas the interplay of hyaluronan in the SC niche with CSC CD44 determines the maintenance of stemness and promotes therapeutic resistance. A better understanding of the molecular mechanisms by which PGs and GAGs regulate CSC function will aid the development of targeted therapeutic approaches which could avoid relapse after an otherwise successful conventional therapy. Chimeric antigen receptor T cells, PG‐primed dendritic cells, PG‐targeted antibody–drug conjugates, and inhibitory peptides and glycans have already shown highly promising results in preclinical models. Abstract : The aberrant expression of proteoglycans (PGs) and glycosaminoglycans (GAGs) in cancer cells and the tumor microenvironment makes an important contribution to tumor progression by modulation of the cancer stem cell (CSC) phenotype and the development of resistance against therapeutic strategies. PGs and GAGs modulate cellular signaling pathways that favor self‐renewal, establishment, and maintenance of CSCs in different niches, with key roles in tumor cell survival, drug resistance, and metastasis.